Makna Pengalihan Hak Kepemilikan Benda Objek Jaminan Fidusia Atas Dasar Kepercayaan - Rachmadi Usman (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The concept of fiduciary in legislation is “the transfer of ownership rights to an object on the basis of belief”, while jurisprudence defines it as “the transfer of property rights based on trust”. However, the object whose ownership rights have been transferred remains in the hands of the fiduciary. This fiduciary concept contains ambiguity, because in its imposition it is not clear how the transfer of property rights to the object of the fiduciary guarantee. The juridical and actual submission of movable objects generally occurs at the same time. The meaning of the transfer of ownership rights to objects of fiduciary security on the basis of this belief needs to be examined. This is a normative legal research using a statutory and historical approach. The results of the study conclude that the real and juridical submission of fiduciary security does not occur at the same time. The transfer of ownership rights to the object of fiduciary security is carried out as collateral for debt repayment, meaning false delivery, not really in the sense of the transfer of real ownership rights. The real delivery only occurs when the fiduciary is deemed in default, on the other hand the object of the fiduciary guarantee will be returned if the fiduciary is not in default. This transfer of ownership rights to the object of fiduciary security is intended to give the fiduciary the authority to act to sell the object of fiduciary security as well as to give preference to other creditors.